Adherence to coprescribing of laxatives with opioids and associated characteristics in general practices in the Netherlands - Karin Hek; Fouzia Lghoul-Oulad Saïd; Joke C. Korevaar; Linda E. Flinterman; Liset van Dijk; Patricia M. L. A. van den Bemt (BMC Primary Care, 2022)
Abstract Background Guidelines recommend to prescribe a laxative with an opioid to prevent constipation. We aimed to determine the adherence by general practitioners (GPs) to this recommendation and to explore which GP- and patient related factors were associated with it from the perspective of the GP.  Methods We conducted an observational study using GPs’ prescription data from the Nivel Primary Care Database combined with a questionnaire asking for reasons of non-adherence. The proportion of first opioid prescriptions prescribed together with a laxative was determined as primary outcome. Possible explanatory factors such as the quality of registration, the level of collaboration with the pharmacy, familiarity with the recommendation and use of a clinical decision support system were explored, as were the self-reported reasons for non-adherence (classified as either GP-related or patient-related). We assessed the association of factors with the primary outcome using univariable multilevel logistic regression analysis. Results The recommendation was measured in 195 general practices. The median proportion of first opioid prescriptions prescribed together with a laxative in these practices was 54% (practice range 18–88%). None of the determinants was consistently associated with the primary outcome. GPs from 211 practices filled out the questionnaire and the most frequently mentioned reason not to prescribe a laxative was that the patient has laxatives in stock, followed by that the patient doesn’t want a laxative; both were patient-related factors. Conclusion There was room for improvement in following the guideline on laxative prescribing in opioid use. A main reason seemed to be that the patient refuses a laxative. Improvement measures should therefore focus on communication between GPs and patients on the relevance of co-using a laxative with opioids. Future studies need to establish the effect of such improvement measures, and determine whether reasons for non-adherence to the guideline changed over time.